The use of pictures for interactional purposes and the grammar of social interaction. (22nd September 2016) - Rasmussen, Gitte
Abstract : This conversation analytic study investigates the introduction of pictures in sequence initial position in Atypical Interaction across institutional and private settings. The pictures share two main features; they are paper-based and they can be manipulated by hand. Danish clients (from different populations) and their relatives, or speech and language pathologists, combine them in initial position systematically with talk, amongst other resources, in three different ways. The paper studies how their use becomes interwoven with talk, and the grammar of language, in order to be understandable as resources for interaction. Co-participants orient towards this, which, as is suggested, needs to be put in the foreground in order to nuance the potential of artefacts not only for atypical interaction, but possibly in typical interaction too. Strands of research in both areas have focused on (the potential of) artifacts as resources for communication and interaction.